Ja przez teatr, czyli o teatrze terapeutycznym dorosłych aktorów z niepełnosprawnością intelektualną i o pewności siebie w działaniu - Stefańska , Anita (Studia Edukacyjne, 2020)
Support for stage creativity and acting in theater therapy is to encourage participants, i.e. adults with intellectual disabilities, not so much to demonstrate theatrical skills and aesthetic sensitivity, but to discover something new in themselves, important for health and psychosocial well-being. In the therapeutic theater, building a spectacle involves overcoming personal limitations and challenging oneself. The potential benefit of this process may be gaining confidence, an important state in the area of social relations. The article aims to indicate the conditions for raising the level of self-confidence of adults with intellectual disabilities who participate in theater therapy and to indicate the consequences harmful for interpersonal relationships, while self-confidence is associated with more negative attitudes towards other people.